Investigation on joint quality of material ASTM A106/API 5L using magnetic impelled arc butt (MIAB) welding - Muhammad, Norasiah; HP Manurung, Yupiter; Kuchuk-Yatsenko, Sergiy; Kachynskyi, Vladimir; Rahman Omar, Abdul; Kassim, Khairulnizam; Zainul Abidin, Azrriq (International Journal of Engineering and Technology, 2018)
Magnetic impelled arc butt (MIAB) welding is a pressure welding process used for joining of pipes with an external magnetic field affecting arc rotation in the small gap along the pipe circumference. This welding process relies on very complex interactions between arc, magnetic field and upsetting force. In this work, investigations are carried out on MIAB welding after preliminary experimentation to understand the basic mechanisms involved in MIAB welding process. The experimental procedure involves a series of trials to develop and evaluate the knowledge base for MIAB welding of seamless pipe. Further, a mechanical testing is carried out on the MIAB welded joints of ASTM A106/API 5L specimen to evaluate its strength and to assess the weld integrity according to API 1104 standard. In addition to the investigation, conceptual Welding Procedure Specification (WPS) and Welding Procedure Qualification Record (WPQR) are developed and presented for pipe welding and for further application identical to this research. The results of the experiment emphasized that the MIAB welded joints exhibited high strength and good weld integrity on the level of base metal of pipe. Hence, MIAB can be considered as the future fast and cost-effective welding process without expensive usage of filler materials and shielding gas.Â